Role of T lymphocytes in tumor response to radiotherapy - Demaria, Sandra; Formenti, Silvia C. (Frontiers in Oncology, 2012)
Over thirty years ago, Helen Stone and colleagues compared the effects of local tumor irradiation in immunocompetent and T cell deficient mice, providing the first evidence that tumor response to radiotherapy is impaired in the absence of a normal T cell repertoire. In the following three decades there has been an exponential growth in understanding T cells and the complex molecular mechanisms that regulate their activation, migration to tumors and effector functions. We now also know that tumor progression is intrinsically linked to the development of multiple immunosuppressive mechanisms that allow cancer cells to escape immune control. Recent evidence about the role of T cells in determining the prognosis and outcome of patients at any clinical stages of cancer has been instrumental in re-directing the concept of immunosurveillance and immunoediting from the realm of preclinical models to the reality of clinical observations. Importantly, cell death induced by standard anti-cancer therapies like chemotherapy and radiation has been demonstrated to involve the immune system and, in certain specific settings, enable a specific immune response. It is, therefore, not surprising that the last few years have seen an increase in investigations exploring how to harness the ability of radiation to induce anti-tumor immune responses. We will review here the experimental evidence that anti-tumor T cells are key players in tumor control achieved by radiotherapy. The effects of radiation on the tumor that have been shown to enhance the priming and effector phases of anti-tumor immunity will be discussed. Finally, we will highlight promising combinations of immune response modifiers that enhance T cell function with radiotherapy which are being tested in the clinic.